How to implement deprescribing into clinical practice. Issue 10 (8th September 2021) - Pruskowski, Jennifer A.; Jeffery, Sean M.; Brandt, Nicole; Zarowitz, Barbara J.; Handler, Steven M.
Abstract: We currently live in the age of medication overload. More than 40% of older adults (≥65 years old) are prescribed ≥5 medications a day and nearly 20% take ≥10. Although medications can provide a wide variety of benefits, the number of medications prescribed is the largest predictor of drug‐drug interactions, nonadherence, and most importantly adverse drug events. Increasingly, patients, caregivers, and health care providers are employing deprescribing efforts as a solution to medication overload. Clinical pharmacists are well positioned to lead and/or contribute to deprescribing efforts. Deprescribing, however, is not commonly and consistently taught within the United States health professional curriculums, and deprescribing infrastructure support is currently limited. The goal of this review is to present a pragmatic approach to pharmacist‐driven clinical practice deprescribing implementation.